2014
DOI: 10.1136/injuryprev-2013-041087
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of core implementation components in team ball sport injury prevention trials

Abstract: The current reporting of core implementation components in team ball sport IPEP trials is inadequate. In many trial reports, it is unclear whether researchers delivered the IPEP directly to players themselves or engaged delivery agents (eg, coaches, physiotherapists, athletic trainers) to deliver the programme. When researchers do interact with delivery agents, the education/instruction of delivery agents should be acknowledged as an intervention component and the delivery agents as an intervention target. Det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 44 publications
1
39
0
Order By: Relevance
“…To maximise preventive impact, IPEP implementation needs to target multiple levels of the team ball sport system, including players (the health beneficiaries), coaches and other staff (the IPEP deliverers) and administrators (the policymakers) 6 8. Reaching the target audience can be enhanced by embedding IPEPs in coach education, using social media and endorsement of IPEPs by sporting organisations and high-profile figures.…”
Section: Reach the Target Audiencementioning
confidence: 99%
“…To maximise preventive impact, IPEP implementation needs to target multiple levels of the team ball sport system, including players (the health beneficiaries), coaches and other staff (the IPEP deliverers) and administrators (the policymakers) 6 8. Reaching the target audience can be enhanced by embedding IPEPs in coach education, using social media and endorsement of IPEPs by sporting organisations and high-profile figures.…”
Section: Reach the Target Audiencementioning
confidence: 99%
“…The RE-AIM framework has been developed to describe five key components to successfully close the gap: Reach, Efficacy, Adoption, Implementation and Maintenance 31 32. A recent review concludes that information on the RE-AIM components in published trials on injury-prevention exercise programmes in team ball sport is scarce, especially regarding the adoption and maintenance of programmes 31…”
Section: Introductionmentioning
confidence: 99%
“…Poor compliance with prevention programs with documented effect may be considered as a potential barrier to implementation, indicating a gap between science and real‐world implementation. The RE‐AIM framework has been developed to describe five key components to successfully close the gap: reach, efficacy, adoption, implementation, and maintenance . The framework is a useful tool that allows decision‐makers to assess how interventions are implemented in practice, and their impact at the individual and organizational levels.…”
Section: Introductionmentioning
confidence: 99%
“…The framework is a useful tool that allows decision‐makers to assess how interventions are implemented in practice, and their impact at the individual and organizational levels. Furthermore, it can help determine which interventions are feasible in real‐world settings . A recent systematic review concluded that information on the RE‐AIM components in published trials on injury prevention exercise programs was insufficient, especially regarding the adoption and maintenance of the programs .…”
Section: Introductionmentioning
confidence: 99%